Outcome of restorative proctocolectomy when the diagnosis is suggestive of Crohn's disease. Issue 10 (October 1993) - Grobler, S P; Hosie, K B; Affie, E; Thompson, H; Keighley, M R
Abstract : Twenty of 81 patients treated by restorative proctocolectomy for presumed ulcerative colitis had some features of Crohn's disease: 10 were classified as definite Crohn's disease and 10 as indeterminate colitis. These pathological features were first apparent during synchronous colectomy and pouch construction in 10 of 11 cases. In the remainder, histological features of possible Crohn's disease were first identified during rectal excision (n = 6), preliminary subtotal colectomy (n = 2), and after pouch excision (= 2). Complications were marginally more common in patients with features of possible Crohn's disease: pelvic sepsis 30% (Crohn's disease 30%, indeterminate colitis 30%) v 20%, fistulas 45% (Crohn's disease 30%, indeterminate colitis 60%) v 16%; ileal stenosis 40% (Crohn's disease 40%, indeterminate colitis 40%) v 21%, pouchitis 50% (Crohn's disease 50%, indeterminate colitis 50%) v 26%, and small bowel obstruction 25% (Crohn's disease 30%, indeterminate colitis 30%) v 13%. Pouch excision or a persistent proximal stoma has been necessary in six patients with possible Crohn's disease (30%) (Crohn's disease 3 cases 30%, indeterminate colitis 3 cases 30%) compared with nine (15%) of the remainder. Median hospital stay, however, was the same and stool frequency in those with a functioning pouch were comparable. These results show that there is a higher complication rate if there are features of Crohn's disease but that the medium term functional results are acceptable if the pouch can be retained.